2017
DOI: 10.22616/rrd.23.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance in forest mineral soils in Latvia modelled with Yasso07 soil carbon model

Abstract: Yasso07 soil carbon model was used to estimate soil carbon balance in dry forest site types (6 site types in total) in Latvia and the results were compared with data from Biosoil2012 soil surveys. Litter input, chemical quality and climatic data are required to run the model. Three different scenarios were used for climate data input-steady climate, climate change + 0.025 °C annually and climate change + 0.05 °C annually. Forest mineral soil is a carbon sink for the whole modelled period-the years of 1990-2030… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Series of studies have also advanced the same understanding following simulation in CENTURY and YASSO models where they have indicated that accumulation of soil organic pools were driven by changes in litter inputs, rate of decomposition, management regimes, root activity, stand growth rates among others. Specifically, plantation management practices like pruning, thinning, liming, drainage, clear felling and timber harvesting among others could also bring the variations on the amount of C as leftovers would decompose differently depending on the site characteristics and on the litter quality of the material [14,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Series of studies have also advanced the same understanding following simulation in CENTURY and YASSO models where they have indicated that accumulation of soil organic pools were driven by changes in litter inputs, rate of decomposition, management regimes, root activity, stand growth rates among others. Specifically, plantation management practices like pruning, thinning, liming, drainage, clear felling and timber harvesting among others could also bring the variations on the amount of C as leftovers would decompose differently depending on the site characteristics and on the litter quality of the material [14,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is limited number of studies addressing effect of drainage of mineral forest soils on the GHG emissions. Modelling approaches usually ignores soil moisture regime assuming that mineral soils are well aerated and the same assumptions are used for wet and dry or drained mineral soils (Bārdulis et al, 2017;Liski et al, 2005;Peltoniemi et al, 2006). However, there are evidences that the drainage of wet mineral soils can increase GHG emissions from forest soils and drainage ditches on mineral soils in boreal forests can emit significant amounts of CH4 and CO2 (Peacock et al, 2021).…”
Section: Introductionmentioning
confidence: 99%